Enhancing work-integrated learning in health sciences higher education: the effect of work self-efficacy and placement preparation - Lin Zhao; Sophia Xenos; Steve Groves; Jing Ye (Higher Education, Skills and Work-Based Learning, 2026)
Purpose This study aims to investigate the impact of work-integrated learning (WIL) on the workplace readiness of healthcare students by examining their work self-efficacy, WIL preparation, perceptions of WIL and their future work prospects. By exploring these factors through the lens of social cognitive career theory, this study seeks to provide a comprehensive understanding of how WIL can be optimised to better prepare students for the demands of their professional careers. Design/methodology/approach This study used a mixed-method survey design involving 103 undergraduate health science students who had completed placement-based WIL experiences. Quantitative measures assessed work self-efficacy, WIL preparation, perceptions of WIL and confidence in future employment, while open-ended-survey questions explored students' experiences, challenges and perceptions of placement-based WIL. Findings Based on 103 students' responses, findings suggest statistically significant positive associations between participants' perceived WIL preparation, work self-efficacy, perceptions of WIL and confidence in future employment. Self-efficacy was the significant predictor of perceived WIL preparation and the strongest contributor to positive perceptions of WIL. Whilst over 85% of students found WIL beneficial in understanding future work relevance and degree applicability, over a third of them raised concerns about a lack of psychological or emotional preparation for the WIL placement. Other challenges merged from qualitative responses included a perceived lack of support from supervisors, difficulty adjusting to workplace environments and substantial resource demands (financial and time-based) associated with balancing placement with other responsibilities. Research limitations/implications The study findings are based on a single university survey with a relatively small sample size which may limit generalisability. Future research should investigate the long-term impact of WIL on employability and career progression, examine placement quality more explicitly and utilise interviews or longitudinal approaches to gain deeper insight into students' experiences. Practical implications Efforts to improve WIL practice outcomes should extend beyond placement allocation and competency attainment to include targeted financial, academic and psychosocial supports before, during and after placement experiences, as well as addressing the structural barriers associated with students’ WIL participation is essential to promoting equitable access, supporting student wellbeing, strengthening work readiness and facilitating successful transition into professional practice. Originality/value This study offers original value by examining the underexplored relationships among work self-efficacy, WIL preparation, workplace readiness and employment confidence within health professional education. The mixed-method findings highlight the importance of psychological preparation, supervisory support and reducing structural barriers to maximise the benefits of placement-based work-integrated learning for workforce readiness.